On the breeding ecology of House Martins Delichon urbica (Linnaeus 1758) in Northeast Algeria. Issue 2 (2nd April 2016) - Hamlaoui, Bochra; Rouaiguia, Meriem; Zebsa, Rabah; Kafi, Fadhila; Haddad, Soumia; Lahlah, Naoual; Houhamdi, Moussa
Abstract: The study of the reproductive biology of House Martins Delichon urbica was carried out in the cities of Guelma and Hammam Debagh, Northeast Algeria during two years 2013 and 2014. Birds of this species produce two broods per year and per breeding pair. At both study sites, the egg-laying period lasted for almost four months. Egg weight and volume differed between broods and years. The mean clutch size was 3.87 ± 1.29, 4.19 ± 1.02 in Guelma and 3.93 ± 1.13, 3.64 ± 1.30 in Hammam in 2013 and 2014, respectively, with a seasonal decline. Hatching success reached 69 and 74.25% in Guelma, and 74.20 and 63.39% in Hammam in 2013 and 2014, respectively. Fledging success was 64.57 and 72.62% in Guelma, whereas, in Hammam it was 72.22 and 58.16% in 2013 and 2014, respectively. Hatching failure was the main cause of mortality. The breeding parameters and morphometrics of the House Martin's eggs in Algeria determined during our study differed from those reported in previous studies carried out in different parts of Europe.